Comparative Study of Simple GA & Hybrid GA for Basis Path Testing under Branch Distance Fitness Function - Garg, Deepak; Kumar, Pardeep (International Journal of Computer Sciences and Engineering, 2025)
Test data generation is a key problem in software testing. Many automatic tools are already present but some are not optimal for large scale, some requires information of local or global solution of problem, some are not suitable to run time conditions. In this paper simple GA & hybrid GA have been implemented to produce automatic data set for testing under basis path testing criteria using branch distance based fitness function in MATLAB. Experimental comparison has been performed first up to twenty five iterations and second up to fifty iterations on same initial population set & then on randomly generated initial population set. After these comparisons conclusion has been made.